Practical implications of objective good faith (Revista do Tribunal Regional Federal da 3ª Região, 2014)
The third millennium couldn’t fulfill itself with a model as antiquate and individualistic as that which marked the end of the nineteenth and beginning of the twentieth century. Both society and State changed – becoming more concerned with the social problems and injustices that “absolute equality” could generate. Civil Law – a mirror of society’s evolution – could not be kept apart from this change. Therefore, its contracts incorporated principles and clauses focused on equity. As a reflex of these changes, the “social function of contracts” and the principle of “objective good-faith” appeared. Both institutes are thoroughly analyzed in this study.
Keywords: contracts; principles; objetive good-faith; civil law